A Three-Surgeon–Six-Hand Operation Using a 4K-3D Exoscope for Neurological Surgery: A Case Report - Tamura, Ryota; Kuranari, Yuki; Katayama, Makoto (Frontiers in Surgery, 2022)
Background: Advances in digital imaging including evolving of 3-dimensional (3D) exoscope has allowed its use as an alternative to microscopes in neurosurgery. The exoscope can concede wide space around the operating table and patient. Here, we show a three-surgeon–six-hand operative approach using a 4K-3D exoscope. Practical advantages and disadvantages of this approach are discussed. Clinical presentation: A 58-year-old male was refered with a 60 mm diameter meningioma in the right frontal convexity. The tumor removal was done by an operator and two assistants with a scrub nurse while viewing images displayed on a 55-inch monitor with integrated 4K and 3D visualization technology retrieved by KINEVO®. Meaningful communication between the operator and two assistants allowed for simultaneous, and precise surgical procedures. Gross total removal was achieved without damaging the brain. Conclusion: The ocular-free, openness of 4K-3D exoscope allows for a three-surgeon–six-handed operation, which leads to simultaneous surgical maneuvers by multiple hands, shorter operative time, flexible/intermittent brain retraction made by two assistants, and educational benefits owing to the surgical procedure being visually shared.